2008
DOI: 10.1016/j.yjmcc.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium limits myocardial infarction in the rat: Dose–response, temporal relations and mechanisms

Abstract: The lanthanide cation, gadolinium (Gd) attenuates post-ischemic myocardial stunning. This study tests the hypothesis that Gd also preconditions the myocardium against infarction following ischemia-reperfusion (IR), and explores potential mechanisms underlying Gd-induced cardioprotection. Regional myocardial infarction was induced in rats by occluding the left anterior descending artery for 30 minutes and reperfusing for 120 minutes. Rats (n = 6/group) were administered intravenous Gd (1 to 100 μmol/kg) 15 minu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Somewhat paradoxically, exogenously added TNF-α is protective during ischemia and reperfusion through mechanisms which involve the JAK/STAT3 pathway, K ATP channels and the mitochondrial permeability transition pore [24,25]. This protective effect of TNF-α may be related to our previous data, which showed that GdCl 3 -induced cardioprotection is dependent upon the activation of JAK-STAT3 and K ATP channels [1]. …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Somewhat paradoxically, exogenously added TNF-α is protective during ischemia and reperfusion through mechanisms which involve the JAK/STAT3 pathway, K ATP channels and the mitochondrial permeability transition pore [24,25]. This protective effect of TNF-α may be related to our previous data, which showed that GdCl 3 -induced cardioprotection is dependent upon the activation of JAK-STAT3 and K ATP channels [1]. …”
Section: Discussionmentioning
confidence: 91%
“…We have previously shown that the optimal cardioprotective dose of GdCl 3 was 20 μmol/kg (Figure 1B) [1]. Therefore, we used this dose for the experiments in this study.…”
Section: Resultsmentioning
confidence: 99%
“…These studies further complicate the role of JAK-STAT pathway in the cardioprotection from the ischemic injury. This finding was also confirmed by the lack of activity of the selective JAK inhibitor (AG-490) in modifying the ischemia/reperfusion injury in vivo [84]. Thus, although the JAK-STAT3 pathway has been included as a key component of the Survivor Activating Factor Enhancement (SAFE) pathway for cardiomyocytes [63], this univocal interpretation should be now considered as more controversial.…”
Section: The Role Of Janus Kinase (Jak)-signal Transducer and Activatmentioning
confidence: 99%
“…Gadolinium (Gd) is a trivalent lanthanide cation able at 10 µM to block stretch-activated calcium channels (1) and to attenuate post-ischemic myocardial stunning (2). It is currently used as a magnetic resonance contrast medium, gadobenate dimeglumine (Gd-BOPTA) (3), but concern for contrast-induced nephropathy has been reported (4).…”
Section: Introductionmentioning
confidence: 99%